Problematika Penerapan Pendekatan Konstruksivisme Model Needham pada Pembelajaran Matematika dan Alternatif Penyelesaian - Mustika, Aulia Musla (Lembaga Penelitian STKIP PGRI Bandar Lampung, 2015)
Mathematics is one of the primary lessons learned at every level of education, from elementary school, high school, even college. This indicates that mathematics plays an important role and should be controlled by each individual. Constructivist learning approach Needham model is expected to condition the student in order to achieve the expected competencies. Problems in mathematical learning approach Needham Model Kostruktivisme appear mainly on the second and third stages of learning. Students difficulty of building their own knowledge because students are accustomed briefed directly by the teacher. As a result, the learning approach Needham Model Kostruktivisme become dull and tiresome. So that the learning objectives can not be achieved optimally. As a problem-solving strategies, the authors offer the following solutions: (1) The condition of learning in groups, (2) the use of props, (3) applying the principle of realistic approach.